2018
DOI: 10.1002/brb3.1076
|View full text |Cite
|
Sign up to set email alerts
|

Brain responses during strategic online gaming of varying proficiencies: Implications for better gaming

Abstract: BackgroundOnline gaming is a complex and competitive activity. However, little attention has been paid to brain activities relating to gaming proficiency.MethodsIn the current study, fMRI data were obtained from 70 subjects while they were playing online games. Based on their playing, we selected 24 clips from each subject for three levels of gaming proficiency (good, poor, and average), with each clip lasting for 8 seconds.ResultsWhen comparing the brain responses during the three conditions, good‐play trials… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
11
0
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 13 publications
(12 citation statements)
references
References 36 publications
0
11
0
1
Order By: Relevance
“…Our findings may also be relevant to informing those interested in maximizing gaming performance in competitive esports. A functional MRI (fMRI) study showed that activation in areas of the brain implicated in executive control was associated with better gaming performance (Wang et al, 2018). Our findings of reduced executive functioning accuracy after hourslong gameplay may indicate the need for breaks in gaming in order to mitigate what might be a type of cognitive fatigue.…”
Section: Discussionmentioning
confidence: 72%
“…Our findings may also be relevant to informing those interested in maximizing gaming performance in competitive esports. A functional MRI (fMRI) study showed that activation in areas of the brain implicated in executive control was associated with better gaming performance (Wang et al, 2018). Our findings of reduced executive functioning accuracy after hourslong gameplay may indicate the need for breaks in gaming in order to mitigate what might be a type of cognitive fatigue.…”
Section: Discussionmentioning
confidence: 72%
“…Specifically, similar to the SST, we would expect the right prefrontal cortex to play a crucial role in stopping performance during the SSG and, in contrast to the SST, other areas more responsible for visual information processing should show increased activity during the SSG [ 65 , 66 , 96 - 100 ]. In addition, recent evidence suggests that performance differences in video games translate to differential brain activity [ 101 ]. Thus, future neuropsychological studies might have to take the individual baseline performance and brain activity into account.…”
Section: Discussionmentioning
confidence: 99%
“…We recruited 103 subjects with IGD (57 males) and 99 recreational game users (RGUs) (51 males) through posters and Internet advertisements ( Table 1). Part of the data in this study comes from our previous study (Wang et al, 2018a(Wang et al, , 2018b with 64 IGD subjects and 63 RGUs. Although there is overlap in subjects, however, all statistical methods are different and the results have no overlap with previous findings.…”
Section: Participantsmentioning
confidence: 99%
“…Internet gaming disorder (IGD) has been defined as a typical behavioral addiction characterized by compulsive game seeking, uncontrolled game playing, and the decision to play despite negative consequences ( Dong, Li, Wang, & Potenza, 2017 ; Petry & O" Brien, 2013 ; Petry et al, 2014 ). In spite of numerous neuroimage studies associated with this condition ( Dong, Lin, Hu, Xie, & Du, 2015 ; Kim et al, 2015 ; Wang, Dong, Wang, Zheng, & Potenza, 2018 ; Zheng et al, 2019 ), the pathological mechanisms of IGD remain elusive. The investigation of the neurobiological substrates of IGD is a fundamental point that will shed light on the underlying mechanisms of the condition.…”
Section: Introductionmentioning
confidence: 99%